2015
DOI: 10.1155/2015/617207
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species, Apoptosis, and Mitochondrial Dysfunction in Hearing Loss

Abstract: Reactive oxygen species (ROS) production is involved in several apoptotic and necrotic cell death pathways in auditory tissues. These pathways are the major causes of most types of sensorineural hearing loss, including age-related hearing loss, hereditary hearing loss, ototoxic drug-induced hearing loss, and noise-induced hearing loss. ROS production can be triggered by dysfunctional mitochondrial oxidative phosphorylation and increases or decreases in ROS-related enzymes. Although apoptotic cell death pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(148 citation statements)
references
References 100 publications
0
135
2
1
Order By: Relevance
“…Induction of apoptosis is a mechanism involved in the action of AMPs (18)(19)(20). Dual staining with AV and PI demonstrated that rates of apoptosis were significantly ROS, typically regarded as toxic products of cellular metabolism, are able to function as signaling molecules that regulate a number of physiological processes (21). ROS are important in the induction of apoptosis in physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of apoptosis is a mechanism involved in the action of AMPs (18)(19)(20). Dual staining with AV and PI demonstrated that rates of apoptosis were significantly ROS, typically regarded as toxic products of cellular metabolism, are able to function as signaling molecules that regulate a number of physiological processes (21). ROS are important in the induction of apoptosis in physiological and pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic trauma damages sensory cells, neurons, and support cells as well as disrupts the microcirculation in the cochlea (Canlon, 1987; Canlon, 1988; Hultcrantz et al, 1987; Kamogashira et al, 2015; Kujawa et al, 2015; Liberman et al, 2015; Ohlemiller et al, 2007; Shi, 2009; Shi et al, 2007; Wang et al, 2002; Yoshida et al, 1999). Increased vascular permeability, reduced circulation (ischemia), aggregation of leukocytes, and injury to endothelial cells are frequently seen in loud sound exposed animals (Goldwyn et al, 1997; Hultcrantz et al, 1987; Lamm et al, 1999; Quirk et al, 1992; Scheibe et al, 1993; Seidman et al, 1999; Shi et al, 2007; Suzuki et al, 2002).…”
Section: Intrastrial Fluid-blood Barrier and Hearing Disordersmentioning
confidence: 99%
“…A variety of drugs, including antibacterial aminoglycoside antibiotics such as gentamicin and amikacin, anticancer agents such as cisplatin, carboplatin, nedaplatin, and oxaliplatin as well as loop diuretics such as furosemide, have side effects that damage the sense of hearing or balance in humans and animals (Ding et al, 2012; Kamogashira et al, 2015; Karasawa et al, 2011; Oishi et al, 2012; Rybak et al, 2007; Schacht et al, 2012). Recent research shows the intrastrial fluid–blood barrier might be a main port of entry for certain ototoxic drugs from the blood into cochlear fluids (Adamson, 2009; Dai et al, 2008; Laurell et al, 2000; Wang et al, 2009).…”
Section: Intrastrial Fluid-blood Barrier and Hearing Disordersmentioning
confidence: 99%
“…Increasing number of studies demonstrated that hearing impairment following cochlear damage due to noise trauma, drug ototoxicity or age-related cochlear degeneration is directly linked to a common pathogenesis involving the formation of ROS [38][39][40][41]. In this way, some studies demonstrated that age-related loss of cochlear hair cells was accelerated in Sod1 mutant mice [42], whereas guinea pig overexpressing catalase in their cochlea significantly protected hair cells and hearing thresholds after ototoxic treatment [43].…”
Section: Mitochondrial Ros In Hearing Lossmentioning
confidence: 99%